Liver injury caused by oral anticoagulants: A population-based retrospective cohort study. - Björnsson, Helgi K; Gudmundsson, David O; Björnsson, Einar S (Liver International, 2020)
To access publisher's full text version of this article click on the hyperlink below Background & aims: Idiosyncratic drug-induced liver injury (DILI) is a rare adverse event. DILI caused by direct oral anticoagulants (DOACs) has been reported, however, data on the risk of DILI are limited. The aim of the study was to evaluate the frequency of DILI caused by oral anticoagulants (OACs) in a population-based setting. Methods: A computerized database search in The National Prescription Database was performed identifying all patients in Iceland who were prescribed OACs (rivaroxaban, apixaban, dabigatran, edoxaban or warfarin) in 2008-2017. Personal identification numbers of these patients were linked with a database containing laboratory results for all hospitals and most outpatient clinics in Iceland. A medical chart review was performed in all cases where onset of liver injury followed intake of OACs. Patients with other specific causes of liver injury were excluded. Causality assessment with the RUCAM method was undertaken in cases with suspected DILI. Results: Three cases of suspected DILI were identified. In all cases, rivaroxaban was the implicated agent among patients prescribed this product (n = 3446). All were women with a hepatocellular type of liver injury. One patient developed a suspected drug-induced autoimmune hepatitis and was treated with corticosteroids. No cases of DILI in patients on warfarin (n = 9101), apixaban (n = 1903), dabigatran (n = 1335) and edoxaban (n = 34) were identified. Conclusions: Rivaroxaban was the only OAC associated with DILI during the 10-year study period. Approximately 1 in 1100 patients treated with rivaroxaban developed DILI. Other OACs were not associated with liver injury in this population-based study. Keywords: anticoagulation; drug reactions; hepatotoxicity. Landspitali University Hospital